The Business Analysis of Fishing Mangroves Crabs (Scylla sp) Using Lift Nets (Pento) In Concong Dalam Village, Concong Subsdistrict, Indragiri Hilir District, Riau Province - Fathur Rahman1; Ridar Hendri; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Study was conducted in march 2016 at Concong Dalam Village, Concong Subsdistrict, Indragiri Hilir District, Riau Province. This study aimed to identify large investment, gross income, operational costs, net income and business feasibility using lift nets (pento) in the village of Concong Dalam. Methods used in research was survey by the number of respondents about 18 people. The average total investment of about 30 units lift net (pento) in the village of Concong Dalam IDR 3.672.778,-. The average total operational costs issued by fishermen as much as IDR 1.739.902,- per month with average gross income received by as much as IDR 6.446.400,- per month.So that fishers can obtain average net income as much as IDR 4.706.496,- per month. The businesses of fishing gear of pento is feasible to developed and continued on based on the value of RCR worth 2,06and value of PPC worth 0,78.Keywords: analysis, fishing, mangrove crabs, pento, Concong Dalam